2013
DOI: 10.1111/jora.12069
|View full text |Cite
|
Sign up to set email alerts
|

The Youth Adventure Programming Model

Abstract: The literature on adventure programming indicates that it is a promising avenue for cultivating positive youth development, but little is known about the conditions that promote positive outcomes. Here, we propose a model for youth adventure programming based on a synthesis of the extant research. The youth adventure programming (YAP) model proposed in this article describes the critical features YAP offers; the experiential learning cycle that occurs within successful programs; and five factors that appear to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 74 publications
1
15
0
Order By: Relevance
“…Research has demonstrated that participant outcomes can be maintained 6 months after the completion of programs (see Bowen & Neill, 2013a;Hattie, Marsh, Neill, & Richards, 1997), but further research is needed to verify the length of time benefits are maintained. Consistent with previous research findings (e.g., Deane & Harré, 2013;Neill, 2001b;Russell, 2003), OAIs in this study most commonly targeted personal development (e.g., improving selfesteem, confidence, independence, well-being), social development (e.g., improving relationships, group cooperation, teamwork), and problem behaviors (e.g., truancy, substance abuse, depression). Although reducing problem behaviors was one of the main OAI goals, staff did not highlight this as a key outcome.…”
Section: Discussion Oais With Youth In Australiasupporting
confidence: 77%
See 1 more Smart Citation
“…Research has demonstrated that participant outcomes can be maintained 6 months after the completion of programs (see Bowen & Neill, 2013a;Hattie, Marsh, Neill, & Richards, 1997), but further research is needed to verify the length of time benefits are maintained. Consistent with previous research findings (e.g., Deane & Harré, 2013;Neill, 2001b;Russell, 2003), OAIs in this study most commonly targeted personal development (e.g., improving selfesteem, confidence, independence, well-being), social development (e.g., improving relationships, group cooperation, teamwork), and problem behaviors (e.g., truancy, substance abuse, depression). Although reducing problem behaviors was one of the main OAI goals, staff did not highlight this as a key outcome.…”
Section: Discussion Oais With Youth In Australiasupporting
confidence: 77%
“…These programs use diverse and innovative practices (e.g., narrative therapy and nature therapy) to seek a variety of outcomes (e.g., psychosocial development and therapeutic treatment) with various client groups (e.g., youth at risk and people recovering from drug abuse; Bandoroff & Newes, 2004). Enhancement of participants' personal and social skills is the most common aim, with some programs seeking more specific outcomes, such as management of behavior problems (Deane & Harré, 2013;Neill, 2001a;Russell, 2003).…”
Section: Outdoor Adventure Interventionsmentioning
confidence: 99%
“…Although several authors have called for a better understanding of the processes that give rise to these effects (Bettmann et al., 2013; Russell & Phillips-Miller, 2002), certain elements have been listed as predictors of positive outcomes (McKenzie, 2003; Panicucci, 2007). These include experimenting with challenge and success through risk-taking (McKenzie, 2003; Priest, 1999), adaptive dissonance (Nadler, 1993; Russell & Phillips-Miller, 2002), and the development of a supportive community (Deane & Harré, 2014; Scheinfeld, Rochlen, & Buser, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These camps exemplify many characteristics of positive youth development (PYD) programs (Sibthorp & Morgan, 2011), fostering personal growth in outcomes such as empowerment, positive values, and positive identity (Norton & Watt, 2014;Thurber, Scanlin, Scheuler, & Henderson, 2007) and creating experiences that promote life skills (e.g., Hattie, Marsh, Neill, & Richards, 1997). However, not much is known about the conditions that promote positive outcomes in adventure programming (Deane & Harré, 2014), especially for diverse groups of youth (Browne et al, 2019). There is a need for more information about the impacts of "less structured, but intense activities" (Rose-Krasnor & Ramey, 2018, p. 688).…”
Section: Introductionmentioning
confidence: 99%